Exploring the dynamics of the refugee phenomenon and it's relevance in South Africa's development : towards the merging of theory and practice for ministry to refugees - Msabah, Barnabe Anzuruni (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2012.